Sureśvara's vārtika on Śārīraka Brāhmaṇa - Hino, Shoun; Jog, K. P. (Motilal Banarsidass Publishers, 2005)
Supercommentary on Śaṅkarācārya's commentary on Br̥hadāraṇyakopaniṣad; includes English translation.